Microbiological assessment of coconut (Cocos nuciferm Linn.) sap with and without tanbark during fermentation. - Donguines, Adelaine Grace Vista
Coconut sap, locally known as tuba, is an alcoholic beverage that has both a low alcohol cntent and short shelf-like. The tuba was analysed in two lots: tuba without tanbark and tuba with tanbark. Different fermentation periods were used: 0-3 hours, 8-11 hours, and 21-24 hours, to determine the physicochemical properties namely, pH, total soluble solids (TSS) and titrable acidity (TA), and microbiological properties namely, total plate count (TPC), acetic acid bacteria (AAB) isolation and lactic acid bacteria (LAB) isolation of tuba without and with tanbark. The physicochemical properties namely, pH, TSS and TA of tuba without tanbark and with tanbark were found to vary as fermentation period progressed. A decreasing pH of 3.78-3.51 was analysed in tuba without tanbark while a decreasing pH of 3.73-3.53 was found in tuba with tanbark. The TSS of both tuba without and with tanbark was also decreasing with a value of 10.2-6.31 and 11.47-8.42 respectively. The TA of both tuba without and with tanbark was increasing with a value of 0.381-0.522 and 0.324-0.469 respectively. One-Way ANOVA showed that all physicochemical characteristics were significantly different (P-value = 0.000) with fermentation time. Two-WAY ANOVA showed that both time and tanbark revealed that there was a significant difference on their effect on the sample (P-value = 0.000). However, only the pH (P-value = 0.000) revealed that there was a significant difference on the interaction of tanbark and time while the TSS (P-value = 0.072) and TA (P-value = 0.696) revealed that there was no significant differences. For the total plate count (TPC) of tuba without and with tanbark, an increasing number of microorganisms was observed. The LAB isolation showed fluctuating results for the number of microorganisms present. The AAB isolation showed an increasing number of microorganisms. Overall, microbiological properties for tuba showed that tuba without tanbark had higher number of microorganisms present compared to the tuba with tanbark in all microbiological analysis. Gram stain technique proved the presence of acetic acid bacteria in the samples. Other microorganisms where also found in the samples including those that resemble the morphological characteristics of lactic acid bacteria. The study showed that physicochemical properties namely, pH and TSS of tuba without tanbark decreases rapidly compared to tuba with tanbark. While for the TA the tuba without tanbark increases rapidly compared to tuba with tanbark. Microbiological analysis showed that the number of microorganisms present in the sample increases more rapidly for tuba without tanbark. Generally, it can be concluded that the presence of tanbark in the sample had an inhibitory effect on the samples, both on the physicochemical and microbiological properties.